Communication without border - Peñaloza Durán, Margarita Rosa; Mojica Acevedo, Eliana Caterine (2025)
The border Juournalism reports, interprets and investigates events between two or more two or more countries with physical spaces in common on economic, cultural, social, sports and political cultural, social, sports and political issues, as well as migration, trade, security, among others, security, among others. On the other hand, migrant or native cybermedia disseminate digital information in an online support, allowing constant updating, because they have the characteristics of updating, because they have the characteristics of multimediality, hypertextuality and interactivity.Venezuela and Colombia share a common border with historical, cultural and migratory ties. Hence, through a descriptive-quantitative quantitative research, with a content analysis, we characterize the journalistic coverage of the content analysis, we characterize the journalistic coverage of the Colombian-Venezuelan border by examining with a purposive sample, the tweets of the social network X of La Opinión (Norte de Santander, Colombia) and La Nación (Táchira, Venezuela) in 2023.
Keywords: Journalism; Border; Information sources; Venezuela; Colombia